2016
DOI: 10.1007/s41042-017-0005-z
|View full text |Cite
|
Sign up to set email alerts
|

Life Satisfaction, Hope, and Positive Emotions as Antecedents of Health Related Quality of Life Among Homeless Individuals

Abstract: Among a sample of individuals identifying as homeless (N′ = 275), this study modeled the relationship between the psychological well-being variables of hope, life satisfaction, positive emotions, and health related quality of life (HRQoL). Specifically, covariance based structural equation modeling (CB-SEM) was used to test a prior theory that life satisfaction serves as an antecedent of HRQoL with hope and positive emotions as mediators. Results indicated that the theorized CB-SEM model closely fit the observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 103 publications
(131 reference statements)
0
15
1
Order By: Relevance
“…Interestingly, while differences in health outcomes (self-rated health, limiting long-standing illness, depressive symptoms, life satisfaction and QOL) between the present sample (ex-homeless) and those who have not been homeless were significant, the magnitude of the associations was smaller than has been documented in previous studies 38. This may be owing to a degree of ‘recovery’ from homelessness.…”
Section: Discussioncontrasting
confidence: 89%
“…Interestingly, while differences in health outcomes (self-rated health, limiting long-standing illness, depressive symptoms, life satisfaction and QOL) between the present sample (ex-homeless) and those who have not been homeless were significant, the magnitude of the associations was smaller than has been documented in previous studies 38. This may be owing to a degree of ‘recovery’ from homelessness.…”
Section: Discussioncontrasting
confidence: 89%
“…Consequently, it buffers against negative influences on eudaimonic wellbeing among people in business or in complex work situations or statuses, which corroborates previous empirical findings for example among the self-employed (Baron et al, 2016 ). These resources are important for sustaining a high level of quality of life and wellbeing among populations in difficult circumstances such as unemployed, homeless, and immigrants (Bak-Klimek et al, 2014 ; Munoz et al, 2016 ). Hence, the strength of psychological resources is essential for individuals in difficult work situations in maintaining a high level of eudaimonic wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that locus of control and psychological capital are psychological resources that enable individuals in different employment statuses to maintain high levels of psychological wellbeing. Such psychological strengths are important to drivers of psychological wellbeing (Lomas, 2019 ; Munoz et al, 2016 ). Psychological capital and particularly internal locus of control are constructs within positive psychology that reflect individual differences in response to events and contexts, therefore important for eudaimonic wellbeing.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Previous research has found hope to be a useful construct in career processes and outcomes such as career exploration, career self-efficacy, and motivation (Hirschi 2014;Valero et al 2015). Hope is also a cognitive resource that facilitates emotional wellness (Munoz et al 2016). Moreover, being engaged in developing and pursuing goals enhances career outcomes, such as increased chances of successful job search (Körner et al 2015) which eventually may translate into success in the STWT as well as perceiving career satisfaction.…”
Section: Psychological Capital and Career Outcomesmentioning
confidence: 99%